Biologic, clinical, and sociodemographic predictors of multi-agent systemic therapy for non-Hodgkin lymphoma in people living with HIV: a population-based investigation in the state of Georgia. Issue 4 (20th March 2020) - Lipscomb, Joseph; Switchenko, Jeffrey M.; Flowers, Christopher R.; Gillespie, Theresa W.; Wortley, Pascale M.; Bayakly, A. Rana; Almon, Lyn; Fernando, Robyn; Ward, Kevin C.
Abstract: We conducted a population-based study of biologic, clinical, and sociodemographic factors associated with receipt of multi-agent systemic therapy (MAST) by people living with HIV (PLWH) who were diagnosed with non-Hodgkin lymphoma (NHL). Building on recent registry-based analyses, we linked records from the Georgia Cancer Registry, Georgia HIV/AIDS Surveillance Registry, and the Georgia Hospital Discharge Database to identify 328 PLWH adults (age ≥ 18) diagnosed with NHL within 2004–2012. Through logistic regression modeling, we examined factors associated with patients receiving MAST for NHL. Robust predictors included CD4 count ≥200 cells/mm 3 around the time of cancer diagnosis, an advanced stage (III or IV) diagnosis of NHL, MSM HIV transmission, and having private health insurance. The strongest single predictor of MAST was CD4 count. Because there is now guideline-integrated evidence that PLWH receiving standard-of-care cancer therapy can achieve substantially improved outcomes, it is vital they have access to regimens routinely provided to HIV-negative cancer patients.